2017
DOI: 10.1111/his.13218
|View full text |Cite
|
Sign up to set email alerts
|

Hypoacetylation of acetyl‐histone H3 (H3K9ac) as marker of poor prognosis in oral cancer

Abstract: The present findings suggest that changes in H3K9ac occur during the process of oral carcinogenesis along with an increase in cell proliferation and EMT. The results demonstrate that H3K9ac may be a useful novel prognostic marker for OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 54 publications
1
54
1
4
Order By: Relevance
“…Lysine acetylation results in relaxation of the chromatin structure, facilitating gene transcription (Momparler 2003;Castilho et al 2017), while deacetylation silences genes by decreasing the accessibility of DNA to transcription factors (Momparler 2003). Deregulation of histone acetylation may cause increased transcription of various genes, and in consequence can lead to malignant transformation (Mancuso et al 2009;Webber et al 2017). Giudice et al (2013) showed that in HNSCC cells, chromatin hypoacetylation occurs, which is evidenced by low level of histone H3 acetylated on lysine 9 (H3K9) in comparison to normal oral keratinocytes.…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Lysine acetylation results in relaxation of the chromatin structure, facilitating gene transcription (Momparler 2003;Castilho et al 2017), while deacetylation silences genes by decreasing the accessibility of DNA to transcription factors (Momparler 2003). Deregulation of histone acetylation may cause increased transcription of various genes, and in consequence can lead to malignant transformation (Mancuso et al 2009;Webber et al 2017). Giudice et al (2013) showed that in HNSCC cells, chromatin hypoacetylation occurs, which is evidenced by low level of histone H3 acetylated on lysine 9 (H3K9) in comparison to normal oral keratinocytes.…”
Section: Histone Acetylationmentioning
confidence: 99%
“…In terms of histone modification, a recent publication showed progressive reduced expression of H39aC in OSCC compared with oral leukoplakia and normal oral mucosa. 7 Similarly, with regard to microRNA dysregulation specifically, alterations in the expression of miR-486-3p, miR-139-5p, and miR-21 were characteristic of OSCC, and their levels were significantly different from those found in normal oral mucosa, implying its biomarker diagnostic potential. 8 DNA methylation and hydroxymethylation, are the most common epigenetic pathways affected in cancer.…”
mentioning
confidence: 99%
“…Approximately 0.6%–61.0% of OLK cases may transform into malignancy (Villa & Sonis, ), and the frequency of OSCC patients associated with OLK when diagnosed varies from 15.8% to 48.0% (Liu et al, ). OSCC had lower level of H3K9ac in comparison with OLK (Webber et al, ). While OSCC and OLK showed similar behavior of H3K4 methylation in comparison with NOE: minimally changed H3K4me1, increased H3K4me2, and decreased H3K4me3 (Mancuso et al, ).…”
Section: Histone Modifications and Opmdmentioning
confidence: 98%
“…H3K9 hypoacetylation was revealed by the analysis of oral rinse samples (Kusumoto et al, ) and OSCC cell lines (Giudice et al, ). Lower H3K9ac indicated poor prognosis by associating with cellular proliferation and epithelial‐to‐mesenchymal transition (EMT) (Webber et al, ) while co‐expression of H3K9ac and mesenchymal vimentin was observed at the invasion front of HNSCC specimens (Giudice et al, ). Conversely, hyperacetylation of H3K9, H3K14, H2AK5 and H3K56 were observed in grade II OSCC cancerous tissues, whereas the level of H4K16ac was low and H4K8ac level was minimally altered (Arif et al, ).…”
Section: Histone Modifications In Osccmentioning
confidence: 99%